The expression profile of genes associated with behavior, stress, and adult neurogenesis along the hippocampal dorsoventral axis in tame and aggressive foxes - Yu. V. Alexandrovich; E. V. Antonov; S. G. Shikhevich; A. V. Kharlamova; L. V. Meister; Y. V. Makovka; D. V. Shepeleva; R. G. Gulevich; Yu. E. Herbeck (Вавиловский журнал генетики и селекции)
The hippocampus plays the key role in stress response regulation, and stress response appears to be weakened in domesticated animals compared to their wild relatives. The hippocampus is functionally heterogeneous along its dorsoventral axis, with its ventral compartment being more closely involved in stress regulation. An earlier series of experiments was conducted with a unique breeding model of animal domestication, the farm silver fox (Vulpes vulpes), which included tame, aggressive, and unselected animals. A decrease in many indices of the hypothalamic–pituitary–adrenal activity was observed in tame animals. Also, adult hippocampal neurogenesis was more intense in tame foxes, and this fact may relate to reduced stress levels in this experimental population of foxes. Nevertheless, the molecular mechanisms responsible for the reduced stress response in tame animals remain obscure. In this study, serum cortisol levels and the mRNA levels of 13 genes in the dorsal and ventral hippocampus have been measured and compared in tame, aggressive, and unselected foxes. At the current stage of domestication, stress-induced cortisol levels in tame, aggressive, and unselected animals differ significantly from each other: tame foxes show the lowest levels, and aggressive ones, the highest. Twelve genes tested demonstrate significant gene expression differences between the dorsal and ventral hippocampi. These differences are mainly consistent with those found in rodents and humans. In tame foxes, significantly elevated mRNA levels were recorded for several genes: CYP26B1 for cytochrome P450 26B1 and ADRA1A for α1A adrenergic receptor in the dorsal hippocampus, whereas the level of NR3C2 mRNA for mineralocorticoid receptor was higher in the ventral. It is presumed that these genes constitute an important part of the mechanism reducing stress induced by contacts with humans and contribute to linking stress regulation with adult neurogenesis in tame foxes and domesticated animals in general.